Connecting Phrases in Arabic Language: Introductive Study - Hisyamuddin Mohd Yusof; Nurul Fatihah Hanafi (Rabbanica: Journal of Revealed Knowledge)
Connection in the Arabic language is essential. Its primary role is to connect issues in the text, which also concerns about text situation, such as to support or to reject or to add some ideas or any other case of the text. Its function is more clear from its different arms for that particular function. One of that necessary arms is connecting phrases which can be categorised as a central pillar of the substantial text; it can make the text colour in the technical aspect, accessible and attractive in reading and diversity of language context. The introductive study about that is needed for teachers and students. This study is to introduce mostly what is the connecting phrases which had mentioned by references. The study is based on descriptive methodology and focuses on the concept of connecting phrases, their particular structures, their roles in Arabic writing and some samples that have been used in al-Quran al-Karim, the study also wants to elaborate more on the importance of the Arabic Language especially in giving accurate and specific meaning for the texts and also to show some results about this study, and the most important of that result is its role in connecting between issues in the text.